KOMUNIKASI INTERPERSONAL DALAM PERBAIKAN MUTU BERKELANJUTAN PENDIDIKAN - Sabarita Banurea (Koordinator Perguruan Tinggi Agama Islam (KOPERTAIS) Wilayah V Aceh, 2022)
The concern of the government and various educational observers has been and continues to strive to improve the quality of education. So, it is not surprising that the development and innovation of education today is increasingly stretched, starting from technology-based learning models, evaluation systems and supervision innovations through sharing application features and so on. However, the communication factor is something that cannot be ruled out, especially schools that are far from urban areas and have difficulty accessing the network. Various communication techniques, such as interpersonal communication, make it easier for teachers to transfer knowledge, so that in the end education is called quality because the scientific quality of students is in accordance with the expectations of the community as recipients of educational services. The results showed that; 1). Interpersonal communication has the potential to carry out an instrumental function as a tool to influence or persuade others, even to maintain a quality of education, 2). Quality of education is the ability to manage schools with the concept of quality management so as to give birth to regeneration with graduation who are ready to enter the social order of society from various fields and activities equipped with expertise, 3). Interpersonal communication is an effort to improve the quality of education, so in order to be able to implement it first understand and understand the concepts and theories. There are at least three dimensions in the application of interpersonal communication to maintain the quality of education; 1). Communication made by the principal both to school residents (internal) and external to the school, 2), communication between teachers, teachers and staff and teachers with operators, 3) communication between teachers and students and parent.AbstrakKepedulian pemerintah beserta berbagai kalangan pemerhati pendidikan telah dan terus menerus berupaya mewujudkan peningkatan mutu pendidikan. Maka tidak heran pengembangan dan inovasi pendidikan dewasa ini semakin menggeliat, mulai dari pembelajaran model berbasis teknologi, sistem evaluasi dan inovasi pengawasan melalui berbagi fitur aplikasi dan seterusnya. Namun demikian faktor komunikasi adalah hal yang tidak bisa dikesampingkan, terutama sekolah yang jauh dari perkotaan dan sulit mengakses jaringan. Berbagai teknik komunikasi, seperti komunikasi interpersonal mengantarkan para guru lebih memudahkan transfer keilmuan, sehingga pada akhirnya pendidikan disebut bermutu karena kualitas keilmuan siswa sesuai dengan harapan masyarakat sebagai penerima layanan pendidikan. Hasil penelitian menunjukkan bahwa; 1). Komunikasi antar pribadi sangat potensial untuk menjalankan fungsi instrumental sebagai alat mempengaruhi atau membujuk orang lain, bahkan menjaga suatu mutu pendidikan, 2). Mutu pendidikan adalah kemampuan mengelola sekolah dengan konsep manajemen mutu sehingga melahirkan regenerasi dengan kelulusan yang siap terjun dalam tatanan sosial masyarakat dari berbagai bidang dan kegiatan yang dibekali keahlian, 3). Komunikasi interpersonal adalah upaya untuk perbaikan mutu pendidikan, maka agar supaya mampu mengimplementasikannya terlebih dahulu mengerti dan memahami konsep maupun teorinya. Setidaknya ada tiga dimensi dalam penerapan komunikasi interpersonal untuk menjaga mutu pendidikan; 1). Komunikasi yang dilakukan kepala sekolah baik kepada warga sekolah (internal) dan eksternal sekolah, 2), komunikasi antar guru, guru dengan staf dan guru dengan operator, 3) komunikasi guru dengan siswa dan orang tua siswa